1981
DOI: 10.1128/iai.34.2.561-570.1981
|View full text |Cite
|
Sign up to set email alerts
|

Localization of chlamydial group Antigen in McCoy cell monolayers infected with Chlamydia trachomatis or Chlamydia psittaci

Abstract: Chlamydial inclusions were demonstrated by indirect immunofluorescence (IF) with antiserum to the chlamydial group antigen when McCoy cell monolayers infected with either Chlamydia trachomatis or Chlamydia psittaci were fixed in formaldehyde or paraformaldehyde, provided the monolayer was not allowed to dry. If these monolayers were then air dried and restained by IF with the same antiserum but with a different fluorescence conjugate, group antigen associated with inclusion-containing McCoy cells but independe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
1

Year Published

1984
1984
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 15 publications
0
24
1
Order By: Relevance
“…Upon screening a panel of monoclonal antibodies by the immunofluorescence staining technique of Richmond and Stirling (26), one antibody was identified, designated 47A2, which stained the surface of chlamydia-infected cells. Determination of the antigenic specificity of 47A2 indicated that it reacted with chlamydial LPS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon screening a panel of monoclonal antibodies by the immunofluorescence staining technique of Richmond and Stirling (26), one antibody was identified, designated 47A2, which stained the surface of chlamydia-infected cells. Determination of the antigenic specificity of 47A2 indicated that it reacted with chlamydial LPS.…”
Section: Discussionmentioning
confidence: 99%
“…A modification of the method of Richmond and Stirling (26) was used to examine chlamydia-infected cultures for the distribution of chlamydial antigens. At different times postinoculation, chlamydia-infected and uninfected control monolayers on cover slips were rinsed with phosphate-buffered saline (PBS) and fixed in either 4% formaldehyde or 4% glutaraldehyde in PBS for 20 min (26). Following brief air drying (30 min) at room temperature, monolayers were treated with dilutions of monoclonal antibodies in PBS for 1 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%
“…Such a mechanism might be important clinically, either by restricting chlamydial-infected cells and the spread of infection, or by playing a role in immunopathology. Initial evidence for the presentation of chlamydial antigen at the host cell surface came from the immunoelectron microscopic demonstration of chlamydial genus-specific antigen, presumably lipopolysaccharide (LPS), at the surface of infected cells and exported from them to adjacent cells (140). However, interpretation of this study is difficult because preliminary air drying or the presence of detergent containing fixative was necessary in order to demonstrate surface antigen, suggesting that the antigen was in hydrophobic micelles not freely exposed at the aqueous surface.…”
Section: Chlamydia1 Antigen Presentation By Infected Cellsmentioning
confidence: 99%
“…Chlamydia genus-speci¢c lipopolysaccharide (LPS) antigen has been observed associated with the cytoplasmic membrane of C. psittaci-and C. trachomatisinfected cell lines by using silver-methenamine staining and electron microscopy [21] as well as indirect immuno£uorescence with polyclonal and monoclonal antibodies [79,80,113]. Additionally, EB envelope antigens have also been detected on the surface of the infected host cell using indirect immuno£uores-cence and polyclonal antibodies [24].…”
Section: Export Of Chlamydia Products Through the Vacuole Membranementioning
confidence: 99%